Analisis Penerapan Akad Ijarah pada Rumah Susun dalam Perspektif Hukum Ekonomi Syariah - Galih Buana Ibrahim; Fauziah Fauziah; Ramiah Lubis (Journal of Sharia and Legal Science, 2025)
The suitability of a building is determined not only by its physical condition, but also by the environment in which it stands. One example is the 26 Ilir Flats, which was initially touted as a modern area in Palembang City. However, the current condition is actually the opposite, where the flats have turned into a slum and are considered uninhabitable. However, these flats are still rented out. This study aims to determine the implementation of the ijarah contract in the 26 Ilir Flats in Palembang City and analyze it from the perspective of Islamic economic law in the context of uninhabitable houses. The research method used is qualitative with an empirical juridical approach. Data were collected through interviews, observations, and documentation with related parties, both apartment owners and tenants. The results of the study indicate deviations in the implementation of the ijarah contract, particularly in aspects of residential suitability that are not in accordance with Islamic principles, such as clarity of benefits and security of the leased object. In a review of Islamic economic law, the implementation of the ijarah contract in uninhabitable houses does not fully meet the requirements for a valid contract due to the lack of clear benefits and security guarantees for the tenant. Therefore, this study recommends the need for supervision and improvement by authorities to ensure that rental contracts are carried out in accordance with the principles of justice, welfare, and transparency as stipulated in Islamic economic law.